The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1111/j.1530-0277.2000.tb01973.x
|View full text |Cite
|
Sign up to set email alerts
|

Binge Ethanol Consumption Causes Differential Brain Damage in Young Adolescent Rats Compared With Adult Rats

Abstract: The young-adolescent brain shows differential sensitivity to alcohol-induced brain damage compared with adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
253
0
7

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 440 publications
(273 citation statements)
references
References 56 publications
11
253
0
7
Order By: Relevance
“…It would be interesting for future studies to investigate in longitudinal studies if an alcohol-specific impairment of response inhibition changes over the course of time when drinking patterns are changing and problem drinking develops. At present, we only know that impulsive behavior and an impairment of response inhibition are risk factors for the development of problem drinking and addictive behavior [22], and it is assumed that this association is reciprocal as chronic alcohol consumption further impairs cognitive control processes [37]. …”
Section: Discussionmentioning
confidence: 99%
“…It would be interesting for future studies to investigate in longitudinal studies if an alcohol-specific impairment of response inhibition changes over the course of time when drinking patterns are changing and problem drinking develops. At present, we only know that impulsive behavior and an impairment of response inhibition are risk factors for the development of problem drinking and addictive behavior [22], and it is assumed that this association is reciprocal as chronic alcohol consumption further impairs cognitive control processes [37]. …”
Section: Discussionmentioning
confidence: 99%
“…Heavy alcohol consumption within a short period of time (i.e., binge drinking) may be particularly detrimental for college-aged students because motivational neurocircuitry underlying risk, reward and decision-making continues to develop during this period (Crews, et al, 2000; Chambers et al, 2003; Monti, et al, 2005). Consistent with this idea, binge ethanol consumption during adolescence in animals is associated with damage of frontal brain areas (Crews et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have demonstrated that ethanol leads to neuronal loss in different brain regions and neuronal loss seems to be associated with cognitive impairment and dementia, neurotransmitter deficiency and mental health issues (Brooks 1997;Brooks 2000;Harper and Matsumoto 2005). Binge ethanol consumption in adult rats leads to neuronal damage in the entorhinal and perirhinal cortices, while in juvenile animals, there also is a marked damage to frontal paleocortical regions (Crews et al 2000).…”
Section: Discussionmentioning
confidence: 98%